(untitled) (Journal of Universal Science Research, 2023)
A varicocele (VAR-ih-koe-seel) is an enlargement of the veins within the loose bag of skin that holds the testicles (scrotum). These veins transport oxygen-depleted blood from the testicles. A varicocele occurs when blood pools in the veins rather than circulating efficiently out of the scrotum.